Essential Fatty Acid Requirements in Tropical and Cold-Water Marine Fish Larvae and Juveniles - Mejri, Sahar Chauffour; Tremblay, Réjean; Audet, Céline; Wills, Paul S.; Riche, Marty (Frontiers in Marine Science, 2021)
To improve survival at early developmental stages of captive fish species, essential fatty acids (EFA) need to be identified. The physiological needs are likely to be different among species using different thermal habitats, because lipids are largely used to maintain cell membrane integrity. This review paper will focus on published research and the main results from our laboratories regarding optimum EFA requirements during young stages in a warm-water marine species, the Florida pompano (Trachinotus carolinus), and a cold-water marine species, the winter flounder (Pseudopleuronectes americanus). To identify the qualitative optimal EFA requirements, we calculated the ratio of each FA in larval or early juvenile tissues to total FA present in the diet. This ratio indicates whether a specific FA from prey is selectively incorporated by larvae and juveniles. Overall, we found that young larvae from both cold- and warm-water species have greater demands for n-3 and n-6 highly unsaturated fatty acids than do larvae at weaning stages. However, the qualitative EFA requirements of the cold-water species at all early developmental stages were higher than those of the warm-water species. Enriched rotifer diets provided relative satisfactory amounts of EFA in Florida pompano, with small selective retention for docosahexaenoic acid (DHA), eicosapentaenoic acid (EPA), and arachidonic acid (ARA), suggesting a potential minor diet deficiency in these EFA. There were higher deficiencies in the cold-water species fed enriched rotifers, as demonstrated by the higher selective retentions of all EFA (DHA, EPA, and ARA), with the exception of larvae fed with copepods. The physiological needs in EFA for juvenile development seemed to be better met for both species when they were fed micro pellets. From the beginning of settlement and in young juveniles, qualitative values of 12% DHA, 10% EPA, 5% ARA, and 40% PUFA of total FA seem to be required for winter flounder juvenile development. In Florida pompano, these requirements could be met until larger juvenile stages, with 15% DHA, 3% EPA, 2% ARA, 2% DPA, and total PUFA below 30% of total FA. This review was done to aid future research aiming to develop nutritionally balanced microdiets or live-prey enrichment diets.